Synthesis, characterization and encapsulation studies of multidentate ligands and their organotin complexes / Nur Adibah Mohd Amin - Nur Adibah , Mohd Amin (2019)
The chemistry of organotin(IV) complexes with multidentate ligands have been the subject of interest because of their potential as an effective antitumor agent. It has been found that the biochemical activity is influenced by the structure of resulting complexes and the numbers of organic groups bind to the tin centre. In this thesis, the work emphasis has been dedicated to synthesis new multidentate ligands and diorganotin(IV) complexes and formulate compound that showing best therapeutic activity. Therefore, a series of multidentate ligands and diorganotin(IV) complexes containing various carbonyl groups as substituents were prepared from the respective ligands with various substituted dibenzyltin(IV) dihalides. The chemical structures of the multidentate ligands and complexes have been characterized and confirmed by melting point, Fourier transform infrared (FT-IR), proton and carbon nuclear magnetic resonance (1H and 13C NMR), ultraviolet and visible (UV‐vis) absorption spectroscopies. The carbon, hydrogen, nitrogen and sulphur (CHNS) elemental analyser was used to determine the elemental composition. In the C10 complex preparation step, crystalline byproduct was formed and its crystalline structure has been identified using X-ray crystallography. Besides that, five ligands and ten complexes have been successfully synthesized. From the structure elucidation data, the coordination of ligands and complexes took place through azomethine nitrogen and phenolic oxygen. For the study of anticancer properties, a selected ligand and corresponding diorganotin(IV) complexes have been tested against several human cancer cell lines specifically breast (MCF-7), lung (A549) and prostate (PC-3). The anticancer screening results showed that most of the complexes had greater therapeutic activity compared to cis-platin. The findings also revealed that complex 2,3-bis((N)-(2,4-dihydroxybenzylidene)amino) maleonitrile di(p-chlorobenzyl)tin, C9 exhibited significantly better activity towards MCF-7 than the other organotin(IV) derivatives. Hence, C9 was chosen for further study on its encapsulation and release. The formulation was prepared using thin film hydration method in phosphate buffered saline (PBS) pH 7.4 as a medium. The properties of the formulation such as the zeta potential, particle size and size distribution profile of the carriers were measured by dynamic light scattering (DLS). The morphology of carrier was visualized by field emission scanning electron microscope (FESEM). The solution of encapsulated-C9 was centrifuged to determine the percentage encapsulation efficiency (%EE). The concentration of C9 in supernatant and sediment were obtained from the measurement with UV-vis spectroscopy. A cationic and non-ionic surfactant mixture was used as drug carrier. The results of formulation showed an average size of 128 ± 22 nm with 100% intensity, 0.5 polydispersity index and the zeta potential is -16 ± 1 mV. From the FESEM image, it was observed that nanoparticles exist in a spherical shape. High encapsulation efficiency and drug loading have been obtained as >90% and 90% respectively. Moreover, in vitro drug release studies showed the release of the drug was observed as soon as the test started but less than 20%, and then followed by a sustained release for 60 days. The amounts of percentage cumulative drug release were found to be 75%. Based on these results, can be conclude that the organotin(IV) complex based on multidentate ligand might be a potential as slow release drug for cancer chemotherapy.